Penerapan Model PBL Berbasis Literasi Berbantuan Media Flinola (Flipbook Inovatif Pancasila) Upaya Peningkatan Pemahaman Nilai-Nilai Pancasila Kelas 2 Sekolah Dasar - Nafiatul Afdhah; Panca Dewi Purwati (Journal on Education, 2025)
Literacy skills significantly influence the learning process and outcomes, making it imperative for teachers to cultivate literacy habits among students. A solid grasp of literacy, coupled with the selection of appropriate learning models and media, is essential for fostering an understanding of Pancasila values. This research aimed to describe the implementation steps of a literacy-based Problem-Based Learning (PBL) model using Flinola (an innovative Pancasila flipbook) and to assess its effectiveness in enhancing second-grade students' comprehension of Pancasila values at SDN Wates 01. A mixed-methods research design was employed. The implementation of the literacy-based PBL model using Flinola was achieved through pre-learning literacy activities and the five phases of PBL. The analysis results indicated that this learning approach was effective in improving students' understanding of Pancasila values, as evidenced by a significant increase in the average score from 56 to 85.2, and a substantial increase in the mastery rate from 16% to 92%. Furthermore, the n-gain analysis revealed a moderate increase in understanding with a value of 0.6953.